Effect of Caries Removal Methods on the Shear Bond Strength of Resin and Glass IonomerAdhesives to Primary Dentin - Mohammadi N; Ferooz M; Eskandarian T; Bagheri R (Shiraz University of Medical Sciences, 2015)
Statement of Problem: There is no enough published data about the shear bond strength of resin modified glass ionomer adhesives on caries-affected primary tooth dentin excavated using minimally invasive systems. Objectives: To evaluate the shear bond strength of 2 different adhesives (one resin modified glass ionomer and one resin) using two caries removal tech- niques on healthy and caries-affected primary dentin. Materials and Methods: Two caries removal methods including mechanical (handpiece) and chemomechanical (Carisolv) techniques and two types of ad- hesives including one resin adhesive (Clearfil SE Bond; CSEB, Kuraray) and one resin-modified glass ionomer adhesive (Riva Bond LC; RBLC, SDI) were used in this study. Ten extracted healthy primary teeth were used for the control group. The teeth were sectioned bucco-lingually and mesio-distally in order to obtain four specimens from each tooth. Thirty suitable specimens were selected as the "control" and randomly divided into two groups of "sound dentin" based on the type of the adhesive used. Sixty extracted caries affected teeth were used for the carious group; sectioned as mentioned above and sixty suitable specimens were selected as the "treatment". Then the specimens were arbitrarily divided into four groups based on caries removal techniques and the type of ad- hesive used (n = 15). After bonding with either CSEB or RBLC, the specimens were restored with a resin composite by means of PVC tubes and subjected to the shear bond strength test. The data was analyzed using ANOVA and Tukey's test. Results: The specimens in Carisolv group bonded with CSEB (11.68 ± 3.1) showed a statistically significant higher mean bond strength followed by those in handpiece group bonded with CSEB (9.4 ± 2.7), which exhibited higher mean values than those groups with RBLC (p < 0.05). Shear bond strength values for Clearfil SE Bond was not significantly higher than Riva Bond LC when used in sound dentin. Conclusions: The lowest shear bond strengths for both adhesives were observed on caries-free dentin.